Иерархия половецкой знати (по погребениям со статусными предметами). - Потёмкина, Т.М. (Степи Европы в эпоху средневековья, 2012)
Социальная стратификация, основанная на неравномерном распределении прав и привилегий, власти, престижа и влияния, обязанностей, собственности, является одним из механизмов, через которые структурируется общество. Социальная структура половецкого общества подвергалась изучению медиевистами неоднократно. В результате среди исследователей средневековых кочевников утвердилось мнение, что не только мужчины, но и женщины-половчанки играли заметную роль в политической и хозяйственной жизни своего народа. Это положение, ставшее практически аксиомой, подтверждено как письменными, так и археологическими источниками. The paper gives a detailed account of the funeral ceremony of Eastern European female and male Polovtsian burials whose grave goods include socially significant objects, such as a cauldron, neck and unbent grivnas or their combinations. Using the data of written records, folklore, and ethnography, the author comes to a conclusion that these deceased were nobles belonging to different, though close ranks in the hierarchy of the Polovtsian society. Syncretism of traditional consciousness enabled one person to combine several functions (i.e. power, military, ritual etc.). However, the general tendency of the Polovtsian social life was to differentiate these functions, which resulted in the appearance of specialised bearers of separate kinds of power. The paper considers a number of debatable points connected with interpretation of an unbent grivna as a rod, with the place of manufacturing these objects, and peculiarities of manifesting these insignia. Ambiguity of ethnocultural correlation of the burials with an unbent grivna exclusively with the Polovtsy has been pointed out.